Size-dependent corrosion behavior and cytocompatibility of Ni–Ti–O nanotubes prepared by anodization of biomedical NiTi alloy. (February 2016) - Hang, Ruiqiang; Liu, Yanlian; Liu, Si; Bai, Long; Gao, Ang; Zhang, Xiangyu; Huang, Xiaobo; Tang, Bin; Chu, Paul K.
Highlights: We fabricated Ni–Ti–O nanotubes (NTs) with different size on NiTi alloy through varying anodization voltages. Worse corrosion resistance and more Ni release are observed from large NTs. Cytocompatibility of NiTi alloy is improved after anodization especially for the sample anodized at 25 V. Abstract: We fabricate Ni–Ti–O NTs with different size on NiTi alloy through varying anodization voltages and evaluate their corrosion behavior, Ni release, and cytocompatibility. Our results show the NTs influence the corrosion behavior and cytocompatibility of NiTi alloy in a size-dependent manner. Worse corrosion resistance and more Ni release are observed from large NTs because of their high specific surface area. However, cytocompatibility is improved after anodization especially for the sample anodized at 25 V. These results thus indicate the release level of Ni ions from NiTi alloy is well tolerated by osteoblasts and surface nanotubular structure contribute to its cytocompatibility.